2020
DOI: 10.1111/bju.15259
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐section of UK prostate cancer diagnostics during the coronavirus disease 2019 (COVID‐19) era – a shifting paradigm?

Abstract: The prostate cancer diagnostic pathway accounts for over 50,000 prostate biopsies each year. (1) In an attempt to minimise the transmission of the COVID‐19 virus, during the height of the COVID‐19 many outpatient and procedural attendances were kept to a minimum in an attempt to safeguard patients and healthcare workers alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Our results are in line with the findings of a survey of 268 urologists in the United Kingdom in April and May 2020, just after the start of the first lockdown period in England, which reported that prostate biopsies were restricted to patients who were suspected to have high-risk disease and that a TP biopsy with a local anaesthetic was typically the preferred method [16].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in line with the findings of a survey of 268 urologists in the United Kingdom in April and May 2020, just after the start of the first lockdown period in England, which reported that prostate biopsies were restricted to patients who were suspected to have high-risk disease and that a TP biopsy with a local anaesthetic was typically the preferred method [16].…”
Section: Discussionsupporting
confidence: 90%
“…[17][18][19] Some examples are limitations of access to screening programmes, to medical care cancer-related visits (both in primary care and in hospitals), to cancer diagnostic tests, reduction in scheduled cancer surgeries due to limited access to postsurgical critical care units and occupation of hospital beds by patients with COVID-19, reduction of treatments that could pose a high risk to the patient in the circumstances of the pandemic, and modifications of therapeutic guidelines, among others. [18][19][20][21] In some countries, a reduction in cancer diagnostics and cancer encounters was observed. [22][23][24] This led to a reduction in new cancer diagnoses and a delay in cancer treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The peak of COVID-19 disruption on the diagnostic pathway of PCa caused a 59.7% drop in prostatespecific antigen (PSA) testing and a decline in the number of centres offering biopsies [6]. A 26% decline for local anaesthetic transperineal (LATP), 59% decline for general anaesthetic transperineal (GATP), and 58% decline for local anaesthetic transrectal (LATRUS) biopsies were seen respectively in the UK [7,8]. The extant literature suggests that both LATP and GATP biopsies lead to fewer complications due to infection or urosepsis, without requiring additional protective measuressuch as the use of prophylactic antibiotics.…”
Section: Adaptations Of Prostate Cancer Diagnostic Pathway During Cov...mentioning
confidence: 99%